Os Confins de Mário Palmério: história e literatura regional - Aidar, Maria Aura Marques (2008)
This dissertation focuses on regional history and literature, using for this the book Vila dos Confins, Mario Palmério, published by Editora Bookstore Jose Olympio, in the year 1956. The aim was to understand the conditions under which it was written, the historical context in which they formed, what was the reception to the book of a politician who treated politics as fiction. The issue that Palmério showed in his narrative was historically formed and registered somehow the social context of its own existence. The literary process of Vila dos Confins was approached by two moments, the writing and the reading. The first one about the relation to the moment of creation, that received influences of the time and society context where Mário Palmério lived; and the second for the receipt and the vitality of the work, the process of reading and interpretation of its readers and critics. In this analysis will find the Confins and its roots, putting the work and researching regionalism as literary movement. Vila dos Confins politicians stratagems and presents frauds occurred in an election for mayor in a small town of Minas Gerais. Palmério wrote a book of his era, considered by some literary critics as a testimonial. Consistent with its social place explained, in the form of fiction, the politics as the Brazilians knew. He brought to the surface the simple life inside of Brazil that found itself in development, but still had its roots and memory. However, although the politics has been dealt with similarity, there was no involvement, was not given ideology. The readers and literary critics gave meaning, they confer on book the readability recognized in themselves and After decipher them, they attributed meaning to the system of signs. They looked to Brazil around them and thought about what they were and where they were. a reception was verified in the sense that it caused and triggered in the receiver, through the text, from simple understanding to the diversity of reactions provoked by it. The year to launch the book was the year of the professionalization of literary criticism in newspapers and magazines and this helped in the large selling of the book. The presence of critical analyses in newspapers and the appearence of literary supplements was highly beneficial to the literature as a whole in the end of this decade.